Laser treatment of SiAlON and surface characteristics. (August 2020) - Yilbas, B.S.; Akhtar, S.S.; Ali, H.; Karatas, C.; Al-Qahtani, H.
Abstract: Laser treatment of SiAlON surface is considered and characteristics of the resulting surfaces are studied incorporating the scanning electron and atomic force miscroscopes, X-ray diffraction and Fourier transform infrared spectroscopy. The wetting state of the laser treated surface is assessed using the droplet contact angle method while the friction coefficient of the treated surface is obtained by using the micro-tribometer. Microhardness and fracture toughness of the treated surface are also measured. Thermal and thermal stress analyses are carried out and temperature and von Mises stress fields are predicted in the laser treated region. It is found that in micro/nano size pillars are formed on the laser treated surfaces, which alters the wetting state from hydrophilic to hydrophobic with contact angle 120° and contact angle hysteresis in the order of 18.2°. In general, laser treated surface is free from large size cracks and voids; however, few locally scattered micro-cracks are observed on the surface. Microhardness increases slightly for the laser treated surface because of the dense layer formed on the surface under the high cooling rates. The fracture toughness of the surface reduces slightly and the friction coefficient of the surface improves after the laser treatment process. The laser scanning tracks, which are closely spaced, result in self-annealing effects in the laser treated region; in which case, von Mises attains low values particularly along the recently formed laser scanning tracks.